Polishing performance of magnetorheological elastomer pad for single-crystal silicon - Changsheng Li; Xiaohong Gao; Yusheng Zang; Zhaoxiang Chen; Jianjun Ding; Shuming Yang; Zhuangde Jiang (Journal of Materials Research and Technology)
Single-crystal silicon optical components are extensively utilized in sophisticated high-end equipment, such as X-ray space telescopes and high-energy laser systems. Despite their widespread use, the ultra-precision polishing of these components is constrained by low processing determinacy and sluggish convergence efficiency. Magnetorheological Elastomers (MREs), renowned for their magneto-mechanical properties were used to prepare polishing pads in this paper, and the performance of MRE material and polishing process of single crystal silicon were investigated comprehensively. It is expected that the polishing efficiency and precision of single-crystal silicon can be improved by the excellent mechanical properties of MREs controllable with magnetic field. Experiments indicate that the mechanical properties of MREs are influenced by the applied magnetic field and preparation parameters, including the magnetic field strength during the pre-structuring process, as well as the mass fraction and size of magnetic particles. Cyclic compression tests demonstrate excellent compression repeatability, demonstrating the potential of MREs as flexible polishing pads. Polishing experiments of single-crystal silicon using MRE polishing pads demonstrate a substantial reduction of surface roughness from an initial Ra of 20 nm–0.373 nm within only 10 min. Following a series of polishing experiments and magneto-mechanical property tests of the elastomers, a multi-parameter coupling model is established for the first time to elucidate the impact of the shear energy storage modulus of MREs on the polishing removal rate and surface roughness of single-crystal silicon. This model provides a foundation for predicting the quality of polished surfaces and optimizing the preparation process of polishing pads.